Guest solvent-dependence of the nanomechanical response in substituted dihydropyrimidinone crystals - Bhandary, Subhrajyoti (2021)
The nanomechanical responses of two crystalline phases of a dihydropyrimidine analogue (1) were similar irrespective of the presence (or absence) of the guest solvent. In contrast, the mechanical responses of two differently solvated forms of the second related (2) crystals were significantly different. These contrasting behaviors are rationalized in terms of intermolecular interactions and energy distributions.